The American Society of Pain and Neuroscience (ASPN) Guidelines and Consensus on the Definition, Current Evidence, Clinical Use and Future Applications for Physiologic Closed-Loop Controlled Neuromodulation in Chronic Pain: A NEURON Group Project - Pope JE; Deer TR; Sayed D; Antony AB; Bhandal HS; Calodney AK; Chakravarthy K; Costandi S; Diep J; Durbhakula S; Fishman MA; Gilligan C; et al. (Journal of Pain Research)
Jason E Pope,1 Timothy Ray Deer,2 Dawood Sayed,3 Ajay B Antony,4 Harjot Singh Bhandal,1 Aaron K Calodney,5 Krishnan Chakravarthy,6 Shrif Costandi,7 Jack Diep,8 Shravani Durbhakula,9 Michael A Fishman,10 Christopher Gilligan,11 Johnathan Heck Goree,12 Maged Guirguis,13 Jonathan Michael Hagedorn,14 Corey William Hunter,15,16 Jan Willem Kallewaard,17,18 Leonardo Kapural,19– 21 Christopher M Lam,3 Sean Li,22 Brian Mayrsohn,23,24 Harold Nijhuis,25 Serge Nikolic,26 Erika A Petersen,27 Lawrence Raymond Poree,28 Shawn K Puri,29 David E Reece,30 Steven Mark Rosen,31 Marc A Russo,32 Jay M Shah,33 Peter Sean Staats,34 Paul Verrills,35 Chau M Vu,1 Robert M Levy,36 Nagy Mekhail37 1Evolve Restorative Center, Santa Rosa, CA, USA; 2Pain Services, The Spine & Nerve Center of the Virginias, Charleston, WV, USA; 3Department of Anesthesiology and Pain Medicine, The University of Kansas Medical Center, Kansas City, KS, USA; 4The Orthopaedic Institute, Gainesville, FL, USA; 5Clinical Research, Precision Spine Care, Tyler, TX, USA; 6Anesthesiology and Pain Medicine, Solaris Research Institute, Wilmington, DE, USA; 7Pain Medicine, Cleveland Clinic, Cleveland, OH, USA; 8Nevada Pain Management, Las Vegas, NV, USA; 9Department of Anesthesiology, Vanderbilt University School of Medicine, Nashville, TN, USA; 10Michael Fishman MD PLLC, Lebanon, PA, USA; 11Robert Wood Johnson University Hospital, New Brunswick, NJ, USA; 12Department of Anesthesiology, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 13Interventional Pain Management Department, Ochsner Health System, New Orleans, LA, USA; 14Department of Anesthesiology and Perioperative Medicine, Mayo Clinic, Rochester, MN, USA; 15Ainsworth Institute of Pain Management, New York City, NY, USA; 16Physical Medicine & Rehabilitation, Icahn School of Medicine at Mount Sinai Hospital, New York City, NY, USA; 17Amsterdam University Medical Centre, Amsterdam, The Netherlands; 18Rijnstate Hospital, Arnhem, The Netherlands; 19Carolinas Pain Institute, Winston Salem, NC, USA; 20Centers for Clinical Research, Winston Salem, NC, USA; 21Chronic Pain Research Institute, Winston Salem, NC, USA; 22National Spine and Pain Centers, Shrewsbury, NJ, USA; 23Interventional Pain Management, Maywell Health, Plainview, NY, USA; 24Interventional Pain Management, Maywell Health, New York City, NY, USA; 25Anesthesiology, St Antonius Hospital, Nieuwegein, Utrecht, The Netherlands; 26Pain Medicine and Neuromodulation, St Bartholomew’s Hospital, Barts Health NHS Trust, London, UK; 27Department of Neurosurgery, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 28Anesthesia- Division of Pain Medicine, University of California, San Francisco, CA, USA; 29Integrated Pain Associates, Killeen, TX, USA; 30Absolute Pain Management, Rockville, MD, USA; 31Delaware Valley Pain and Spine Institute, Trevose, PA, USA; 32School of Biomedical Sciences, University of Newcastle, Newcastle, NSW, Australia; 33Samwell Institute of Pain Management, Colonia, Livingston, and Englewood, NJ, USA; 34National Spine and Pain Centers, Atlantic Beach, FL, USA; 35Metropain, Melbourne, VIC, Australia; 36Neuromodulation: Technology at the Neural Interface, International Neuromodulation Society, Boca Raton, FL, USA; 37Evidence-Based Pain Management Research, Cleveland Clinic, Cleveland, OH, USACorrespondence: Timothy Ray Deer, The Spine and Nerve Center of the Virginias, 400 Court Street, Charleston, WV, 25304, USA, Tel +1 304 347 6141, Email doctdeer@aol.comIntroduction: Neuromodulation has been a staple of treatment for moderate-to-severe chronic refractory pain since the introduction of the first spinal cord stimulator by Norman Shealy in 1967. Appreciating the dynamic nature of electrical modulation of the nervous system from the epidural space, the goal has been consistent, reliable, and therapeutic neural activation of the spinal cord. This has proven to be extremely difficult. Recently, the Food and Drug Administration (FDA) released a guidance on physiologic closed loop controlled (PCLC) devices, highlighting the potential for these therapies to deliver accurate, consistent, real-time therapy, enhancing medical care and reducing variability. Because of the growing neuromodulation market focus on PCLC strategies, the American Society of Pain and Neuroscience (ASPN) sought to develop guidance on safety and efficacy, along with a taxonomy surrounding PCLC systems (PCLCSs) and to develop an evidence-based best practice review.Methods: A librarian-assisted literature search was performed to identify manuscripts relevant to the topic of PCLC stimulation for management of chronic pain. Initial literature search was performed utilizing MEDLINE, EMBASE, Cochrane database, BioMed Central, and Web of Science. Included manuscripts encompassed meta-analyses, systematic reviews, randomized controlled trials (RCTs), prospective or retrospective studies with follow-up to 12 months, limited to the English language. MESH terms utilized included “closed-loop”, “physiologic closed loop controlled”, “spinal cord stimulation”, “closed loop feedback”, “feedback controlled”, “neuromodulation”, “pain”, “persistent pain”, “neuropathic pain”, and “chronic pain”. The modified USPSTF evidence and recommendation grading strategy previously utilized was again employed.Results: Four studies were identified for review, 2 prospective, one retrospective, and one randomized controlled study with at least 12-month follow-up.Conclusion: PCLC neuromodulation is an innovation that requires a responsible introduction. As commercial access grows, there is a responsibility that requires consistency with definition, evidence generation, focused on safety and efficacy.Keywords: spinal cord stimulation, closed loop stimulation, physiologic closed loop stimulation, clinical evidence review, neuropathic pain, chronic pain, neuromodulation